Konstruksi Makna Smartphone bagi Mahasiswa Jurusan Marketing Komunikasi di Universitas Bina Nusantara Jakarta - Ferane Aristrivani Sofian (Bina Nusantara University, 2015)
Most Marketing Communication students are smartphone users. The students, either consciously or not, would prefer to use his/her smartphone rather than socializing with other people around. Even when in class during lectures, until it often leads to conflict between lecturer and students. In connection with the meaning, everyone will behave towards something based on the meaning of that something in his mind. Thus, this study would like to try to answer what the meaning of the smartphone for Marketing Communication students is; why they use a smartphone when lectures take place; and what their opinion in wisefully using of their smartphones. This study used a qualitative research system with a descriptive case study method. Through observation and in-depth interviews of nine informants can be seen that the meaning of a smartphone for students is as practical communication medium for sharing information and the necessities of life; teaching methods oflecturer are less attractive, boredom, always wanted to connect anytime, anywhere with friends or family, addicted to smartphones are reasons why students always want to use smartphones in class when the lecture takes place; and the wise use of smartphones by students is at the right time, do not harm others and for positive things.